Attitudes towards health and safety at the workplace in Lithuania : a report to stakeholders - Woolfson, Charles; Beck, Matthias; Sceponavicius, Audrius (Glasgow, 2002)
"While a number of 'first wave' accessing countries have now closed most of the formal chapters in the EU accession process, the gap between legislative transposition and implementation capacities remains in certain key areas of the social acquis. Questions of effective workplace social dialogue in Central and Eastern Europe, especially as regards health and safety in the workplace remain to be addressed.